Análisis e impacto de la contabilidad ambiental en la sostenibilidad financiera y organizacional de las Micro, Pequeñas y Medianas Empresas (MIPYMES) en la ciudad de Santa Marta, durante el periodo 2021-2023 (2024)
The research focuses on the impact of Environmental Accounting on the organizational sustainability of Micro, Small and Medium Enterprises (MSMEs) in Santa Marta, Colombia. Environmental Accounting, as a tool to measure and manage environmental impacts, is examined from its theoretical foundations to its practical implementation in local companies. The study seeks to identify challenges and opportunities in the adoption of Environmental Accounting by MSMEs, evaluating its influence on business decision-making and regional sustainable development. The research will contribute to knowledge about the integration of environmental accounting practices in the specific context of Santa Marta, offering valuable information for entrepreneurs, policy makers and other actors interested in promoting business sustainability in similar environments. Ultimately, the research seeks to drive effective strategies to foster organizational sustainability and economic development in the region.